Energy risk measurement and hedging analysis by nonparametric conditional value at risk model - Li, Ling; Hu, Guopeng (Frontiers in Energy Research, 2022)
The accurate measurement and management of energy risk have become important issues of the economic development and energy security for all countries. The existing literature generally adopts the Value at Risk (VaR). However, VaR does not satisfy the subadditivity axiom to measure the energy risk, which makes the calculation defective. In this paper, we use the Conditional VaR (CVaR) with the characteristics of coherent and convex risk measurement to measure energy risk under nonparametric kernel (NPK) framework. We consider how to use the energy derivatives to hedge the price risk of energy so that the result is more reasonable and effective. The empirical results show that the NPK method that we propose is more effective to measure the actual energy risk and carry out more effective risk hedging.